Analysis of the Potential of Sago Flour Processing (Metroxylon) in Supporting the Sago Bioindustry (Waraka Sago) in Waraka Village, Central Maluku Regency - Limahuey, Rafie; Lasaiba, Mohammad Amin; Riry, Roberth Berthy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Waraka Country is one of the sago-producing countries in Maluku Province, especially Central Maluku Regency. The potential of sago that can be developed optimally is sago starch. Bioindustry is an effort made to manage agricultural and natural resources such as sago management, which is carried out with the help of technology to produce various products that have high economic value and can help the economy of sago farmers. The type of research used is descriptive qualitative; the variable in this study is a single variable. Waraka is one country with the potential for sago, which can be developed and appropriately utilised to increase income, meet the community's needs, and create the SAWA bioindustry. The processed products of sago flour in the SAWA bioindustry are refined Sago Flour, Sago Noodles, and Sago Rice. There are 2 Stages of the Sago Flour Production Process to support the SAWA (Sago Waraka) bioindustry in Negeri Waraka, Central Maluku Regency, namely the wet sago production process and the sago flour production process by SAWA bioindustry. The SAWA bioindustry (Sagu Waraka) needs sago flour to produce damp sago flour from sago producers every time they produce 200-220 sacks. The SAWA bioindustry needs wet sago flour from 30-35 sacks from the producers to the SAWA bioindustry (Sagu Waraka).